Case of acute abdomen due to acute pancreatitis: a uncommon presentation of leptospirosis - Sharma, Zubin Pradeep; Sharma, Divya; Sharma, Ravindra (International Journal of Research in Medical Sciences, 2019)
Even though, Leptospiral infection is not rare, it can have different rare presentations. Acute pancreatitis is one such uncommon gastrointestinal manifestation of acute pancreatitis. Apart from the classic clinical features, elevated serum lipase, along with radiological proof and positive leptospiral serology confirms this infrequent association.